Evaluation of Pharmaceutical Services and Drug Use (PKPO) in Hospital Pharmacy Installation - Susiyarti Susiyarti; Gunawan Pamudji; Iswandi Iswandi (Sarana Ilmu Indonesia (salnesia), 2022)
Good and professional service is a hope for all levels of society, especially health services in hospitals, especially pharmaceutical services and drug use. The research was conducted at the Pharmacy Installation of the Mutiara Bunda General Hospital of Brebes. The purpose of this study was to determine the level of conformity of the seven PKPO standards to SNARS Edition 1 and their improvement strategies based on the priority of the percentage of achievement of accreditation and hospital needs. This research was a non-experimental research design, data collection using PKPO survey instruments with interview and observation methods. The research subjects were pharmacists and other pharmacy installation staff. The data result were processed in tabular form, the level of conformity of each PKPO standard was compared to SNARS Edition 1 of 2018 with a minimum standard of 80%. The results of the PKPO level of conformity at the Pharmacy Installation of RSU Islami Mutiara Bunda was not fully in accordance with SNARS. The percentages were obtained PKPO 1 of 100%, PKPO 2 of 8,00%, PKPO 3 of 69,04%, PKPO 4 of 84,61%, PKPO 5 of 80,0%, PKPO 6 of 100% and PKPO 7 of 87,50 %. Based on the percentage of achievement and the level of need for IFRS, the priority order of improvement strategies that need to be immediately carried out by hospitals are PKPO 3 standards, namely storage, PKPO 2 standards regarding selection and procurement, then PKPO 7, PKPO 4 and PKPO 5.